PWE-005 High resolution anorectal manometry: first study establishing normal values in healthy volunteers. (28th May 2012) - Burke, J M; Jackson, W; Withers, M M; O'Grady, H; Duthie, G S
Abstract : Introduction: High Resolution Anorectal Manometry (HRAM) combined with interpretive software allows for the interpolation of manometric recordings into highly detailed topographical plots of intraluminal pressure events. HRAM has previously been shown to correlate highly with conventional water perfused manometry measurements. 1 This preliminary study is the first report establishing HRAM pressures in healthy volunteers. The advantages of the detection of pressure changes over a longer length of the anal canal have already been shown to improve accuracy and the detection of abnormalities in the anorectum. 2 Methods: HRAM was performed using the Medical Measurement System (Enschede, Netherlands) consisting of an 8-channel HRAM catheter with sensors spaced at 0.8 cm intervals. Pressure data are displayed in topographic form using Medical Measurement System analysis software that is integrated into the system. Measurements of anal sphincter pressure at rest, cough, during voluntary squeeze, endurance squeeze and pushdown were evaluated. Volunteers also completed a questionnaire which provided a Wexner score. Results: A total of 20 healthy volunteers (11 Female, 9 Male) with a mean age of 40 (range 19–60) constituted the study population. The Wexner scores ranged from 0 to 1 (median 0). Conclusion: These preliminary measurements of HRAM pressures in healthy volunteers could serve as a valuable resource of normative data when performing HRAM studies in disease specific groups such as incontinence and constipation. Competing interests: None declared. References: 1. Jones MP, Post J, Crowell MD. High-resolution manometry in the evaluation of anorectal disorders: a simultaneous comparison with water-perfused manometry. Am J Gastroenterol 2007;102 :850–5. 2. Rao SS . Advances in diagnostic assessment of fecal incontinence and dyssynergic defecation Clin Gastroenterol Hepatol 2010;8 :910–19.